Analysis of patients attitude to undergo urgent endoscopic procedures during COVID-19 outbreak in Italy. Issue 7 (July 2020) - Armellini, E.; Repici, A.; Alvisi, C.; Dinelli, M.; Gambitta, P.; Manes, G.; Mutignani, M.; Orlando, S.; Radaelli, F.; Salerno, R.; Venezia, G.; Verna, C.; et al.
ABSTRACT: We conducted a survey to investigate to what extent the fear of COVID-19 has influenced the patients decision to undergo or to cancel endoscopic procedures. We collected data from 847 patients from 13 centres. The main indication for endoscopy was anemia, followed by pain and unexplained weight loss. The percentage of not presenters progressively increased throughout the three weeks of study, from 15.1% at the beginning to 48.2% at the end. 37 (34.2%) upper GI endoscopies and 112 (56.3 %) colonoscopies showed an organic cause explaining the symptoms presented by the patients, respectively; 5 cases of gastric cancer (4.6%) and 16 cases of colorectal cancer (CRC) (6.0%), respectively, were detected; during the second week the percentage of organic diseases found at upper endoscopy was 19 (33.3%) with 5 cancer (8.7%), and 61 (49.1% ) at colonoscopy, with 2 CRC (1.6%); finally, during the third week the corresponding figures were 19 (48.7%) for upper GI examinations, with 3 gastric cancers (7.7%), and 43 (60.5%) with 4 (6.5%) CRC cases found.We conclude that patients weighted the fear of having a clinically relevant disease with the fear of becoming infected by coronavirus, and a relevant percentage of them (29.4%) decided not to attend the endoscopy suites at the scheduled date.